Solvothermal synthesis of uniform and high aspect ratio of CdS nanowires and their optical properties - Phuruangrat A. (2014)
Uniform and high aspect ratio CdS nanowires (NWs) were successfully synthesized by the solvothermal reaction of the solution containing Cd(NO 3) 2, (NH 4) 2S and ethylenediamine (NH 2(CH 2) 2NH 2). In this research, the effects of molar contents of the stating materials, reaction temperatures and lengths of time on phase, vibration modes, morphologies, and optical properties of the as-synthesized products were studied using XRD, Raman spectroscopy, SEM, TEM, SAED, HRTEM, UV-vis spectroscopy and PL spectroscopy. They were found to be controlled by the contents of the stating materials, reaction temperatures and lengths of time. Mixed nanoparticles and short nanorods of CdS were synthesized by the 200 °C and 24 h solvothermal reaction of the solutions containing 0.0001-0.0050 mol of the starting materials. Upon increasing the content of the starting materials to 0.0100 mol, the completely uniform CdS NWs with aspect ratio of >250 were synthesized. © 2012 Elsevier Masson SAS. All rights reserved.